Inhibitory Effect of Fingolimod on Head and Neck Squamous Cell Carcinoma and Its Mechanism: Gene Set Enrichment Analysis: GSEA for mechanism of Fingolimod on HNSC - Chang, Lemeng; Xie, Chunhua; Chou, Kaiping; Meng, Qingnan; Zhao, Lihui (Cellular and Molecular Biology, 2023)
This study aimed to clarify the therapeutic effect of Fingolimod on head and neck squamous cell carcinoma (HNSC) and initially explore its mechanism through data mining, clinical sample analysis and basic experiments. The normalized Enrichment Score (NES) of Fingolimod in tumor tissues was obtained by SwissTargetPrediction and The Cancer Genome Atlas (TCGA) database. IC50 (50% inhibitory concentration) of Fingolimod for HNSC was verified based on the Genomics of Drug Sensitivity in Cancer (GDSC) database. SCC9 cells were cultured in vitro for the application of Fingolimod. Cell proliferation was determined by the Cell Counting Kit-8 (CCK-8). The expression levels of genes were determined by reverse transcription-polymerase chain reaction (RT-PCR). The molecular regulatory mechanism of Fingolimod acting on HNSC was analyzed with WebGestalt. Cyclin expression was determined by Western blot assay. The key targeted genes for Fingolimod against HNSC were screened with the TCGA database and verified in clinical samples. Gene Set Enrichment Analysis (GSEA) showed the highest NES score in HNSC (NES=1.53, P<0.05). GDSC showed the lowest IC50 in Fingolimod SSC9 cells. IC50 calculated by the cell activity detected by CCK8 was 4.34 μmol/L, and RT-PCR showed significantly suppressed expression of proliferation-related gene Ki-67 after adding Fingolimod (P<0.05). Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed that the targeted genes for Fingolimod were mainly enriched in cell cycle-related pathways. Western blot showed significantly decreased cyclin expression in SSC9 cells after the treatment with Fingolimod (P<0.05). TCGA analysis revealed that PLK1 is a key targeted gene for Fingolimod in the treatment of HNSC. RT-PCR showed the significantly increased activity of SCC9 after over-expressing PLK1, and the increased proliferation and anti-apoptosis abilities (P<0.05), as well as the significantly inhibited expression of Ki-67 and Bcl-2 after adding Fingolimod. Fingolimod can promote the arrest in G0/G1 of SCC9 cells, and PLK1 is a key targeted gene for the treatment of HNSC. Fingolimod can inhibit cell proliferation caused by PLK1 over-expression.